A Neuroscientific and Cognitive Literary Approach to the Treatment of Time in Calderón’s Autos sacramentales - Rodríguez Villar, Alejandra Juno (Frontiers in Integrative Neuroscience, 2022)
Time processing is a fundamental subject in cognitive sciences and neuroscience. Current research is deepening how our brains process it, revealing its essential role in human functionality and survival. In his autos sacramentales, Early Modern Spanish playwright Pedro Calderón de la Barca portrays the relationships between human inner workings and the Christian concept of time. The processes that Calderón ascribed to the soul of his characters in the 17th century today reveal themselves coincidental with ongoing cognitive and neuroscientific findings. These plays perform the experiencing of the present, the perception of the flow of time, the measure of time from ranges that go from seconds to eternity, and the mental travel necessary to inhabit the past and future with the help of memory and imagination. Calderón explores how the dramatic form can portray all those phenomena and how that portrait constrains the dramatic structure. The different parts of the brain in charge of executive decisions, projections, memories, computation, and calibration are the basis that leads these characters to make the choices that will take them to the future they have cast for themselves.